MODEL PEMBELAJARAN JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR IPAS PADA SISWA KELAS 5 SD - Flora, Delya; Sholeh, Agus; Setia Budi, Eko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This classroom action research aimed to improve the learning outcomes of fifth grade students in Integrated Science and Social Studies (IPAS) through the implementation of the Jigsaw cooperative learning model. The study was conducted at SDN Karangbesuki 4 Malang with 29 students as subjects. The research design followed the Kemmis and McTaggart model consisting of planning, acting, observing, and reflecting stages in two cycles. Data were collected through tests and non-test techniques, including observation and documentation. The results showed that the average score increased from 66.03 in the pre-cycle to 76.03 in Cycle I and 85.14 in Cycle II. The percentage of students achieving mastery also improved from 31.03% in the pre-cycle to 62.07% in Cycle I and 82.76% in Cycle II. These findings indicate that the Jigsaw learning model effectively enhanced student participation, responsibility, and comprehension of biodiversity material. Therefore, the Jigsaw cooperative learning model can be recommended as an alternative strategy to improve IPAS learning outcomes in elementary schools.